Multi‐dimensional modeling of solar cells with electromagnetic and carrier transport calculations. (2nd February 2012) - Li, Xiaofeng; Hylton, Nicholas P.; Giannini, Vincenzo; Lee, Kan‐Hua; Ekins‐Daukes, Ned J.; Maier, Stefan A.
ABSTRACT We present a multi‐dimensional model for comprehensive simulations of solar cells (SCs), considering both electromagnetic and electronic properties. Typical homojunction and heterojunction gallium arsenide SCs were simulated in different spatial dimensions. When considering one‐dimensional problems, the model performs carrier transport calculations following a Beer–Lambert optical absorption approximation. We show that the results of such simulations exhibit excellent agreement with the standard PC1D one‐dimensional photovoltaic simulation. Photonic and plasmonic attempts to enhance SC efficiency demand comprehensive electromagnetic calculations to be undertaken in order to acquire accurate carrier generation profiles in two and three‐dimensional systems. Our model provides complete spectral and spatial information of typical optical and electronic behavior. Furthermore, our approach permits the detailed investigation of complex systems, including plasmonic SCs, which cannot be simulated using low‐dimensional modeling tools. We present the results of numerical simulations of an optically thin plasmonic gallium arsenide SC and observe improved device performance arising from the application of plasmonic nanostructures, which agree well with previous experimental findings. Copyright © 2012 John Wiley & Sons, Ltd.